2017
DOI: 10.1016/j.ridd.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Measuring social skills of children and adolescents in a Chinese population: Preliminary evidence on the reliability and validity of the translated Chinese version of the Social Skills Improvement System-Rating Scales (SSIS-RS-C)

Abstract: The Social Skills Improvement System-Rating Scales (SSIS-RS; Gresham & Elliott, 2008) are designed to assist in the screening and classification of students (aged 5-18 years) who are suspected of presenting with social skills deficits and to offer guidelines in the development of interventions to remediate those types of problems. The objective of this study is to examine the preliminary reliability and validity of the translated Chinese version of the SSIS-RS, referred to as the SSIS-RS-C. In this study, pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 21 publications
2
21
0
6
Order By: Relevance
“…The lack of appropriate social skills mostly demonstrated by students within the categories which exhibit externalizing behavior, such as autism, intellectual disability, slow learner, and Down syndrome. This result is in line with Cheung, Siu, Brown (2017), who found that persons with ASD may have difficulty in making friends as one of the assertive behavior, and total lack of facial expressions as one of the empathy skills. Yeo & Teng (2015), also suggested that ASD have social skills deficits fall under the areas of behavioral and affective.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The lack of appropriate social skills mostly demonstrated by students within the categories which exhibit externalizing behavior, such as autism, intellectual disability, slow learner, and Down syndrome. This result is in line with Cheung, Siu, Brown (2017), who found that persons with ASD may have difficulty in making friends as one of the assertive behavior, and total lack of facial expressions as one of the empathy skills. Yeo & Teng (2015), also suggested that ASD have social skills deficits fall under the areas of behavioral and affective.…”
Section: Discussionsupporting
confidence: 90%
“…The lack of appropriate social skills exhibit by children identified as learning disabilities, autism, emotional and behavior impairments, intellectual impairments, and attention deficit/hyperactivity disorders tend to have lower social skills. (Kavale & Mostert., 2004;Cheung., Siu, Brown., 2017). As for visually impaired students they were also having difficulty in social interaction (Salleh & Zainal., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Their creations included interesting additions and shapes. Fostering social skills: The participants were very interested in building organs out of playdough and using microscopes. Although there are many different methods to assess social skills (Cheung et al, 2017), some of the well‐known components of learning‐related social skills in children were observed in these activities. These included cooperation, sharing, following directions, participating appropriately in groups, staying on task, and organizing work materials (Liu et al, 2010).…”
Section: Aims Of the Sessions' Activitiesmentioning
confidence: 99%
“…The results showed that the Cronbach’s ɑ coefficients of all social skills subscales on the SSIS‐RS showed good value across parent‐reported, teacher‐reported, and self‐reported forms (except Communication scale on the student form, α = 0.68) in a sample of elementary school children. Cheung, Siu, and Brown () explored the applicability of SSIS‐RS in the Chinese context. In their study, they compared the SSIS‐RS American norms with the Hong Kong participant sample, and their findings provided helpful insights into the cross‐cultural utility and applicability of the SSIS‐RS subscales.…”
Section: Introductionmentioning
confidence: 99%